Model-driven GUI generation and navigation for android BIS apps - Silva, S. (2022)
This paper presents our approach for producing graphical user interfaces (GUIs) for functionally rich business information system (BIS) prototypes, upon a mobile platform. Those prototypes are specified with annotated UML class diagrams. Navigation in the generated GUIs is allowed through the semantic links that match the associations and cardinalities among the conceptual domain entities, as expressed in the model. We start by reviewing the Android scaffolding for producing flexible GUIs for mobile devices. The latter can present rather different displays, in terms of size, orientation and resolution. Then we show how our model-based generative technique allows producing prototypes that match both the Android GUIs requirements, while implementing our model-driven approach for user navigation.